Depression among Saudi international university students and its associated risk factors - Mohammed Abdullah Alnaim; Abdullah Hamdan Alghamdi; Mohammed Rashid Aljawair; Faisal Abdulaziz Alhadi; Abdullah Mohammed Alomair; Ali Alsaad (BMC, 2024)
Abstract Introduction Depression disorders are one of the most widespread mental disorders among college students. In university students, depression has been associated with lower academic performance, worse work performance, and increased dropout risk. his study aims to assess the prevalence of depression and highlight risk factors among Saudi international university students (IUS) in the United States (US), the United Kingdom (UK), and Australia. Subject and methods This cross-sectional study was conducted among Saudi students who chose to study abroad. A self-administered online questionnaire was sent to the students using an online survey. The questionnaire includes socio-demographic data (e.g., age, gender, specialty, etc.), medical characteristics, social status, and the Patient Health Questionnaire (PHQ-8) to assess the student's depression. Results Of the 401 students, 52.4% were younger (age 18 - 25 years), and more than half were males (53.9%). Most of the participants were studying in the US (46.6%), followed by the UK (40.6%) and Australia (12.7%). The rate of major depression among Saudi students studying abroad was 40.4%. In univariate analysis, major depression was influenced by age, marital status, specialty, personal and family history of mental illness, contact with family and friends, and feeling like a stranger. However, after conducting multivariate regression analysis, previous diagnoses of mental illness and feeling a stranger were identified as the significant independent risk factors for major depression. Conclusion This study provides insights into the prevalence and risk factors associated with depression among Saudi IUS. The prevalence of major depression among Saudi IUS was 40.4%. Previous history of mental illness and feeling like strangers were identified as the most prominent risk factors in this study. Identifying the prevalence and contributing factors of depression can guide academic institutions and governments in the development of effective interventions and support for IUS's mental well-being. Future research could diversify the sample and employ longitudinal designs.